Steering Control Method for an Underactuated Unicycle Robot Based on Dynamic Model. (18th November 2018) - Jin, Hongzhe; Zhang, Yang; Zhang, Hui; Liu, Zhangxing; Liu, Yubin; Zhu, Yanhe; Zhao, Jie
Abstract : This paper proposes a lateral balancing structure based on precession effect of double-gyroscopes and its associated control strategy of the steering for an underactuated unicycle robot. Double-gyroscopes are symmetrically designed on the top of the unicycle robot and utilized to adjust the lateral balance of system. Such design can inhibit the disturbance of the gyroscope system to the pitch angle and is beneficial to maintain the lateral balance in the case of large roll angle fluctuations. Based on the analysis of the dynamics model, the gyroscope precession effects will be caused by the angular velocity of the bottom wheel and the roll angular velocity, i.e., resulting in a torque in the direction of the yaw. Then, a rapid response control strategy is proposed to use the torque to control the steering. Simulation results demonstrate the rationality of the lateral balance structure and the feasibility of the steering control method.